On the encapsulation and viability of probiotic bacteria in edible carboxymethyl cellulose-gelatin water-in-water emulsions. (February 2018) - Singh, Poonam; Medronho, Bruno; Miguel, Maria G.; Esquena, Jordi
Abstract: In this study, novel biobased dispersions to entrap probiotic bacteria were developed and characterized regarding their formation, microstructure and in vitro viability and culturability performance in model salivary, gastric and intestinal fluids. The systems are composed of type B pigskin gelatin and sodium carboxymethyl cellulose (NaCMC) which, depending on concentrations and temperature, can form water-in-water (W/W) emulsion droplets as observed by optical and fluorescence microscopy. Model probiotic bacteria, Lactobacillus rhamnosus GG (LGG), were successfully entrapped into the W/W emulsion droplets with surprisingly high viability. Moreover, the survival of the LGG cells, when exposed to the different model fluids, was improved after their entrapment in the W/W emulsions. Therefore, the developed dispersions display high potential for probiotic encapsulation and eventual delivery into the intestinal tract with acceptable viability. Graphical abstract: Highlights: Novel promising biobased matrices for probiotic bacteria entrapment and delivery. Water-in-water emulsions (W/W) of gelatin and carboxymetyl cellulose were prepared. Formation, structure, viability and in vitro performance accessed. Successful incorporation of viable probiotic bacteria into W/W emulsions. Enhanced in vitro survival of entrapped LGG cells in the W/W emulsions.